KUALITAS PELAYANAN UJI BERKALA KENDARAAN BERMOTOR PADA UPT. PENGUJIAN KENDARAAN BERMOTOR (PKB) DI TAMIANG LAYANG KABUPATEN BARITO TIMUR KALIMANTAN TENGAH - Dedy Saputra; Taufik Arbain; Muhammad Riduansyah Syafari (stiatabalong.ac.id, 2021)
This study aims to analyze Motorized Vehicle Testing Service Quality at the UPT PKB Kabupaten Barito Timur and to analyze what are the supporting factors and inhibitors of Motorized Vehicle Testing Services at the UPT PKB Kabupaten Barito Timur.The research approach used is descriptive qualitative method, to describe the condition of the subject / object of research based on facts that appear or as they are. Data collection is done by observation, interview, and documentation techniques.Motorized Vehicle Testing Services at UPT PKB at Barito Timur Transportation Service is one of the public service institutions that carries out services on vehicle feasibility testing. As a public institution, it is mandatory to provide quality services, so as to provide satisfaction to the recipients of the service. The definition of Motorized Vehicle Testing (PKB) itself is an examination of the vehicle condition, whether the vehicle meets the requirements of land-worthy or not, including the completeness of vehicle documents, given the enormous benefits of public or non-public transportation equipment helping mobility of community activities.The results showed that the service quality of UPT PKB Kabupaten Barito Timur was inadequate or still low, because it was found that most of the five quality indicators were still low, especially indicators of reliability, responsiveness, assurance and empathy. The factors that influence are internal factors and external factors . Internal factors consist of organizational structure, human resources / apparatus, small service and financial systems, while external factors are in the form of budgeting policies and placement of personnel from related institutions without looking at needs and competencies.